2019
DOI: 10.1097/mlr.0000000000001023
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination and Population Health Management Strategies and Challenges in a Behavioral Health Home Model

Abstract: Objective: Behavioral health home (BHH) models have been developed to integrate physical and mental health care and address medical comorbidities for individuals with serious mental illnesses (SMIs). Previous studies identified population health management capacity and coordination with primary care providers (PCPs) as key barriers to BHH implementation. This study examines the BHH leaders’ perceptions of and organizational capacity to conduct these functions within the community mental health programs impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Qualitative data and surveys have shown that BHH staff value the access they have gained through the program to the state's health information exchange (HIE). 8,9 The state's HIE notifies the BHH when one of their enrollees experiences an emergency department visit or hospitalization. 8,9 With this tool, BHHs can initiate contact with hospital staff to facilitate a smoother discharge plan.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Qualitative data and surveys have shown that BHH staff value the access they have gained through the program to the state's health information exchange (HIE). 8,9 The state's HIE notifies the BHH when one of their enrollees experiences an emergency department visit or hospitalization. 8,9 With this tool, BHHs can initiate contact with hospital staff to facilitate a smoother discharge plan.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The state's HIE notifies the BHH when one of their enrollees experiences an emergency department visit or hospitalization. 8,9 With this tool, BHHs can initiate contact with hospital staff to facilitate a smoother discharge plan. BHH staff also reported investing in developing stronger relationships with hospital staff in charge of discharge planning and care coordination so that they could respond effectively when their enrollees were hospitalized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations